The contribution of secondhand tobacco smoke to blood lead levels in US children and adolescents: a cross-sectional analysis of NHANES 2015-2018 - Alexander Obeng; Taehyun Roh; Anisha Aggarwal; Kido Uyasmasi; Genny Carrillo (BMC, 2023)
Abstract Background Lead is a major developmental neurotoxicant in children, and tobacco smoke has been suggested as a source of lead exposure in vulnerable populations. This study evaluates the contribution of secondhand tobacco smoke (SHS) to blood lead levels (BLLs) in children and adolescents. Methods We analyze data from 2,815 participants aged 6-19 years who participated in the National Health and Nutrition Examination Survey (2015-2018) to investigate the association between serum cotinine levels and BLLs. A multivariate linear regression was conducted to estimate geometric means (GMs) and the ratios of GMs after adjusting for all covariates. Results The geometric means of BLLs in study participants aged 6 − 19 years were 0.46 µg/dl (95% CI 0.44, 0.49). After adjusting for relevant participant characteristics, the geometric means of BLLs were 18% (BLL 0.48 µg/dl, 95% CI 0.45, 0.51) and 29% (BLL 0.52 µg/dl, 95% CI 0.46, 0.59) higher in participants who had intermediate serum cotinine levels (0.03 − 3 ng/mL) and those who had high serum cotinine levels (> 3 ng/mL) respectively, compared to participants who had low serum cotinine levels (BLL 0.41 µg/dl, 95% CI 0.38, 0.43). Conclusions SHS exposure may be a source of BLLs in US children and adolescents. Efforts to reduce lead exposure in children and adolescents should include strategies to reduce SHS exposure.